The Division of Joint Property in the Form of Song Royalties (A Case Study of Decision Number 16/Pdt.G/2024/PTA.JK) - Annisa' Nailis Saadah; Luthfiyah Trini Hastuti; Solikhah (MultiTech Publisher, 2025)
This article aims to analyze the methodology of royalty distribution in divorce cases and assess Decision Number 16/Pdt.G/2024/PTA.JK, regarded as the first legal precedent in Indonesia for dividing royalties as joint marital property upon court-declared dissolution of marriage. The analysis is based on John Rawls's and MH Kamali's theories of justice. Using normative research methods, the article examines statutory provisions regulating the rights and obligations of divorcing couples and evaluates the court decision in question. The findings indicate that royalties qualify as joint marital property since they are intangible assets derived from rights. The division of joint property is carried out equally, in accordance with Articles 96 and 97 of the Islamic Law Compilation. This decision reflects justice for the parties involved, as both contributed to the song creation process.